2006
DOI: 10.3310/hta10480
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the ventricular assist device programme in the UK

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. NHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 71 publications
(163 reference statements)
1
45
0
Order By: Relevance
“…24 A detailed description of resource use data and unit cost estimates can be found in the original article 23 and associated Health Technology Assessment report. 1 Briefly, data were collected for surgical procedure and subsequent stay in the intensive care unit (ICU) and cardiac ward, HT assessment, HT procedure and associated ICU and ward stay, follow-up readmissions to the ICU or ward, outpatient visits, investigations, blood tests, and drugs. Resource use data were also collected for all adverse events.…”
Section: Economic Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 A detailed description of resource use data and unit cost estimates can be found in the original article 23 and associated Health Technology Assessment report. 1 Briefly, data were collected for surgical procedure and subsequent stay in the intensive care unit (ICU) and cardiac ward, HT assessment, HT procedure and associated ICU and ward stay, follow-up readmissions to the ICU or ward, outpatient visits, investigations, blood tests, and drugs. Resource use data were also collected for all adverse events.…”
Section: Economic Analysis Methodsmentioning
confidence: 99%
“…1 As a result of the high mortality rate associated with conventional therapy while awaiting HT, which is mainly pharmacologic with intravenous inotropic agents, left ventricular assist devices (LVADs) have been proposed as a life-saving alternative for patients with hemodynamic decompensation. [2][3][4] In 2008, the United States (US) Food and Drug Administration (FDA) approved the LVAD HeartMate II 5 (Thoratec Corp, Pleasanton, CA) for use as a bridge to HT (BTT) in candidates at risk of imminent death from non-reversible LV failure.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are some reports of related studies, the cost effectiveness of VAD implantation surgery for end-stage heart failure [5][6][7][8][9] has not been sufficiently evaluated in the context of the medical system of certain counties. In particular, there is a need for a comparative economic evaluation of extracorporeal and implantable VADs and a socioeconomic evaluation of long-term use of VADs.…”
Section: Introductionmentioning
confidence: 97%
“…46) Another meta-analysis showed an ICER of $89,790-$414,274 per QALY for LVAD over heart transplantation for end-stage heart failure. 47) These data suggested that LVAD is not cost-effective for endstage heart failure.…”
Section: Left Ventricular Assist Device (Lvad)mentioning
confidence: 99%